Case Report: Chemotherapy, immunotherapy, and radiotherapy achieve complete response for metastatic ureteral urothelial carcinoma with significant squamous differentiation - Bi, Ying; Li, Jun; Qu, ShangHu; Yin, Jun; Zhu, Yong; Zhang, ChongJian; Bai, Yu (Frontiers in Oncology, 2026)
BackgroundThe majority of tumors in the upper urinary tract are classified as urothelial carcinomas, with only 15% exhibiting different levels of squamous differentiation, known as the squamous subtype. These tumors tend to be more aggressive and are associated with a worse prognosis compared to standard urothelial carcinomas.Case presentationA 60-year-old man was found to have cancer in his left ureter and subsequently underwent a robot-assisted laparoscopic procedure to partially remove the left ureter and perform a ureterovesical anastomosis. The postoperative analysis revealed high-grade urothelial carcinoma with marked squamous differentiation(40% squamous differentiation) and microsatellite stability (MSS). Three months after surgery, the abdominal incision recurred and abdominal mass resection was performed again. One month after abdominal surgery, imaging evaluation showed lymph node metastasis in the left lower wall of the bladder and retroperitoneum.Ultimately, the patient attained complete imaging remission following treatment with the \GC\ chemotherapy regimen, along with \tislelizumab\ immunotherapy and radiotherapy.ConclusionThe \GC\ chemotherapy protocol, along with \tislelizumab\ immunotherapy and radiotherapy, shows remarkable effectiveness in treating metastatic ureteral urothelial carcinoma with significant squamous differentiation.